Nursing Students’ Perception on Tutor Performance and Students’ Critical Thinking in PBL Online - Muhammad Fahri; Lisa Musharyanti (IJNP (Indonesian Journal of Nursing Practices), 2021)
Background: The COVID-19 pandemic has influenced health education in many countries, including nursing education that moves to online learning.  It has affected the tutor's performance and students' critical thinking skills, especially in online PBL tutorials. Tutor and nursing students have to re-adapt to a new online meeting atmosphere that previously had face-to-face meetings. There was no previous investigation into the effect of online PBL on tutor performance and nursing students’ critical thinking skills in UMY.Purpose: This study aims to determine students’ perceptions of tutor performance in online problem-based learning tutorials and the critical thinking skills of nursing students in UMY.Methods: This research is a cross-sectional quantitative study. The sample included 91 second-year nursing students, using the total sampling technique. The researchers used two questionnaires with closed questions about the tutor's performance in PBL tutorials and the critical thinking skills. Data were analyzed by univariate analysis. Result: The majority of respondents were female (83.5%) and 19-20 years old (91.2%). The study results showed that the tutor's performance on the online PBL tutorial was good (95.6%), while the critical thinking ability was poor (54.9%).Conclusion: This study showed that students still needed to adjust and adapt maximally to online problem-based learning tutorials and needed support and motivation to improve the quality of learning.